Datos sobre la Vitamina K - R. Elaine Turner (EDIS, 2007)
FCS8666-Span, a 2-page fact sheet by R. Elaine Turner, is the Spanish version of "Facts about Vitamin K" (FCS8641). It explains the importance of vitamin K in our diets, how much we need, and how to get this vital nutrient. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.